Pelecitus tercostatus (Molin, 1960) (Nematoda, Onchocercidae) in Amazona vinacea (Aves, Psittaciformes) from Argentina: Morphological details and clinical findings - Diaz, Julia Inés (2012)
Pelecitus tercostatus (Molin, 1860) (Onchocercidae, Dirofilariinae) was found in the leg of a Vinaceous-breasted Parrot Amazona vinacea (Aves, Psittaciformes) from Misiones, Argentina. The present report enlarges the host distribution of the species and represents the first record of any nematode in A. vinacea. The macroscopic lesions produced in the bird are also described.